2020
DOI: 10.1109/tits.2019.2913589
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Access Management for Cooperative Intersection Control

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Furthermore, mathematical modeling approaches have been studied by formulating optimization problems [11]- [17]. The optimization problem is formulated to minimize vehicle travel time and vehicle crossing time within an intersection that uses vehicle positions and speeds to numerically solve under constraints such as collision avoidance and speed limits.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Furthermore, mathematical modeling approaches have been studied by formulating optimization problems [11]- [17]. The optimization problem is formulated to minimize vehicle travel time and vehicle crossing time within an intersection that uses vehicle positions and speeds to numerically solve under constraints such as collision avoidance and speed limits.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The ICU comprehensively considers all vehicle information and assigns an appropriate passing time to each vehicle. In order to capture the effective relative motion law of vehicles and describe the dynamic platoon related to each lane at intersections, an advanced hybrid queuing model was proposed in [14]. This model designed a traffic management method based on model predictive control to minimize the travel time of vehicles at the intersection.…”
Section: A Unsignalized Autonomous Intersection Managementmentioning
confidence: 99%
“…For instance, Yang et al ( 20 ) proposed an algorithm for finding the optimal departure sequence to minimize the total delay for various stages of connected vehicle technology, namely, conventional vehicles, connected vehicles, and AVs. Similarly, Medina et al ( 21 ) formulated a mixed-integer linear program based on model predictive control that also optimizes the sequence of vehicles crossing an autonomous intersection. Using model predictive control, Kamal et al ( 22 ) showed that the smoothness of traffic flow can be improved as well at signal-free intersections.…”
mentioning
confidence: 99%
“…In some studies, only one vehicle is allowed to pass the merging zone at a time with a fixed speed ( 29 , 30 ), limiting the intersection management efficiency. Other studies have to deal with the complexity induced by mixed-integer decision variables ( 21 , 32 ), which we avoid in our framework because only vehicle acceleration (not necessarily an integer) is considered as the control variable. In addition, it would be beneficial to define a comprehensive objective function that ensures a desired level of system performance for both intersection throughput and traffic smoothness.…”
mentioning
confidence: 99%